Temperature, precipitation, birch and fireweed chemistry, and moose (Alces alces) calf mass in northern Sweden (Sveriges lantbruksuniversitet, 2023)
Data och R-kod används i styckvis strukturell ekvationsmodellering för en studie som jämförde de direkta och indirekta effekterna av temperatur och nederbörd på kalvvikt för älg i norra Sverige. Studien inleddes 1988 i ett försök att undersöka klimatförändringarnas effekter på vanliga foderarter för den ekonomiskt och kulturellt viktiga älgen i Sverige. Den pågick till 1997 och startades om 2017. Temperatur- och nederbördsvariabler är härledda från SMHI väderstationsdata. Genomsnittlig kalvvikt för älg för undersökningsplatser härleds från data från Svenska Jägareförbundet och enskilda jaktlag. Både väder- och kalvvikt representerar medelvärden inom en radie på 50 km från varje studieplats. Mätningar av kväve och neutrala detergenter är resultatet av nära infraröd spektroskopimodellering, med 50 prover för att kalibrera modellen. Prover togs från 1-ha platser och inkluderade material från 30 individer av antingen dunbjörk eller mjölkört. Se beskrivning på engelska. Data and R code used in piecewise structural equation modelling for a study that compared the direct and indirect impacts of temperature and precipitation on moose calf mass in northern Sweden. The study was initiated in 1988 in an effort to examine the impacts of climate change on common forage species of the economically and culturally important moose in Sweden. It ran until 1997 and was re-started in 2017. Temperature and precipitation variables are derived from SMHI weather station data. Average moose calf mass for study sites is derived from data from the Swedish Hunter's Association and individual hunting teams. Both weather and moose calf mass represent mean values within a 50km radius of each study site. Nitrogen and neutral detergent fibre measures are the result of near-infrared spectroscopy modelling, using 50 samples to calibrate the model. Samples were collected from 1-ha sites and included material from 30 individuals of either downy birch or fireweed. The dataset contains the following files. DataWeatherVegMoose.tsv is the data itself ...